LBA4 Association of KRAS mutational status with response to pembrolizumab monotherapy given as first-line therapy for PD-L1-positive advanced non-squamous NSCLC in KEYNOTE-042. (15th December 2019) - Herbst, R S; Lopes, G; Kowalski, D M; Kasahara, K; Wu, Y-L; De Castro, G; Cho, B C; Turna, H Z; Cristescu, R; Aurora-Garg, D; Lunceford, J; Kobie, J; et al.
Abstract: Background: Somatic KRAS mutations are detected in approximately 15%-30% of lung adenocarcinomas, with regional variation, and are associated with poor prognosis. We explored the prevalence of KRAS mutations and their association with efficacy in participants (pts) with non-squamous NSCLC enrolled in the KEYNOTE-042 study of pembrolizumab monotherapy vs platinum-based chemotherapy as first-line therapy for advanced PD-L1-positive (TPS ≥1%) NSCLC (NCT02220894). Methods: KRAS mutational status and tumor mutational burden (TMB) were assessed by whole-exome sequencing (WES) in pts with who had available tumor and matched-normal tissue. This exploratory analysis included descriptive analyses of the correlation between KRAS mutational status and shifts in distributions of TMB and PD-L1 expression and the association of KRAS and KRAS G12C status with efficacy. Results: Of the 782 pts with non-squamous histology, 301 (38%) were evaluable by WES and had matched tumor and normal DNA. KRAS mutations were identified in 69 (23%) pts, including 29 (10%) G12C carriers. Pts with vs without KRAS mutation tended to have higher PD-L1 TPS (median [IQR] 60% [10-95] vs 35% [10-80]) and TMB (median [IQR] 191 [129-288] vs 105 [56-226] mut/exome). Outcomes of pembrolizumab and of chemotherapy for pts with and without KRAS mutation and for KRAS G12C carriers are in the table. Of note, CIs were wide given the modest frequency of KRAS mutation and low frequency of KRAS G12C. Conclusion: Findings of this descriptive exploratory analysis suggest that pembrolizumab monotherapy should be considered as a standard first-line treatment option for PD-L1-positive advanced non-squamous NSCLC regardless of KRAS mutational status. These findings also suggest that a pembrolizumab-containing regimen is a clinically relevant comparator for studies of KRAS -targeted therapy given as first-line treatment of NSCLC. Clinical trial identification: KEYNOTE-042; NCT02220894. Editorial acknowledgement: Joanne Tomassini and Melanie Leiby, both of Merck & Co., Inc., Kenilworth, NJ, for writing support. Legal entity responsible for the study: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Funding: Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure: R.S. Herbst: Advisory / Consultancy: Abbvie Pharmaceuticals; Advisory / Consultancy: ARMO Biosciences; Advisory / Consultancy, Research grant / Funding (self): AstraZeneca; Advisory / Consultancy: Biodesix; Advisory / Consultancy: Bristol-Myers Squibb; Advisory / Consultancy, Research grant / Funding (self): Eli Lilly and Company; Advisory / Consultancy: EMD Serrano; Advisory / Consultancy: Genentech/Roche; Advisory / Consultancy: Genmab; Advisory / Consultancy: Halozyme; Advisory / Consultancy: Heat Biologics; Advisory / Consultancy: Infinity Pharmaceuticals; Advisory / Consultancy: Loxo Oncology; Advisory / Consultancy, Research grant / Funding (self): Merck & Co., Inc., Kenilworth, NJ, USA; Advisory / Consultancy: Nektar; Advisory / Consultancy: Neon Therapeutics; Advisory / Consultancy: NextCure; Advisory / Consultancy: Novartis; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Sanofi; Advisory / Consultancy: Seattle Genetics; Advisory / Consultancy: Shire PLC; Advisory / Consultancy: Spectrum Pharmaceuticals; Advisory / Consultancy: Symphogen; Advisory / Consultancy: Tesaro; Advisory / Consultancy: Tocagen; Officer / Board of Directors: Junshi Pharmaceuticals. G. Lopes: Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): EMD Serono; Research grant / Funding (institution): Merck & Co., Inc.. D.M. Kowalski: Advisory / Consultancy, Research grant / Funding (institution): MSD; Advisory / Consultancy: Boehringer-Ingelheim; Advisory / Consultancy: Roche; Advisory / Consultancy: Pfizer; Advisory / Consultancy: BMS. K. Kasahara: Research grant / Funding (institution): MSD. Y-L. Wu: Advisory / Consultancy, Research grant / Funding (institution): Boehringer-Ingelheim; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Roche; Advisory / Consultancy, Research grant / Funding (institution): MSD; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self): Eli Lilly; Honoraria (self): Pierre Fabre; Honoraria (self): Pfizer; Honoraria (self): Sanofi. G. De Castro Jr.: Honoraria (self), Honoraria (institution), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Roche; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: MSD; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: BMS; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Pfizer; Honoraria (self), Honoraria (institution), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Merck Serono; Honoraria (self), Honoraria (institution), Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Boehringer-Ingelheim; Honoraria (self), Honoraria (institution): Novartis; Honoraria (institution): Amgen; Honoraria (institution): Astellas. B.C. Cho: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution): AstraZeneca; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy: Roche; Speaker Bureau / Expert testimony: Bristol Myers Squibb; Speaker Bureau / Expert testimony, Research grant / Funding (institution): MSD; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): Yuhan. H.Z. Turna: Research grant / Funding (institution): MSD. R. Cristescu: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. D. Aurora-Garg: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. J. Lunceford: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. J. Kobie: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. M. Ayers: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. M.C. Pietanza: Shareholder / Stockholder / Stock options, Non-remunerated activity/ies: Merck Sharp & Dohme. B. Piperdi: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck Sharp & Dohme. T.S.K. Mok: Honoraria (self), Advisory / Consultancy, Leadership role, Research grant / Funding (institution): AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): BMS; Advisory / Consultancy, Research grant / Funding (institution): Clovis Oncology; Research grant / Funding (institution): Eisai; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): MSD; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Novartis; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Roche; Advisory / Consultancy, Research grant / Funding (institution): SFJ Pharmaceuticals; Research grant / Funding (institution): Taiho; Research grant / Funding (institution): Xcovery; Honoraria (self), Advisory / Consultancy: Roche/Genentech; Honoraria (self), Leadership role, Shareholder / Stockholder / Stock options: Hutchinson MedPharma; Honoraria (self): Janssen; Honoraria (self): Takeda; Honoraria (self): Fishawack Facilitate Ltd; Advisory / Consultancy: Eli Lilly; Advisory / Consultancy: Merck Serono; Advisory / Consultancy: ACEA Biosciences Inc.; Advisory / Consultancy: Celgene, Vertex, geneDecode, OncoGenex, Ignyta; Leadership role, Shareholder / Stockholder / Stock options: Sanomics Ltd; Advisory / Consultancy, Shareholder / Stockholder / Stock options: Cirina; Non-remunerated activity/ies, ASCO board of directors: ASCO; Non-remunerated activity/ies, track chair for ESMO 2019: ESMO.